2014
DOI: 10.1021/cn500015s
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Growth on l- and d-Cysteine Self-Assembled Monolayers Reveals Neuronal Chiral Sensitivity

Abstract: Studying the interaction between neuronal cells and chiral molecules is fundamental for the design of novel biomaterials and drugs. Chirality influences all biological processes that involve intermolecular interaction. One common method used to study cellular interactions with different enantiomeric targets is the use of chiral surfaces. Based on previous studies that demonstrated the importance of cysteine in the nervous system, we studied the effect of L-and D-cysteine on single neuronal growth. L-Cysteine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…The ability of biomolecules to distinguish between D and L configurations is crucial in all biological events, including cell‐cell, cell‐proteins and cell‐bacterial interactions . Nearly all mammalian lectins prefer the D‐form over the L‐form of carbohydrates, the exceptions to this is L‐fucose and L‐iduronic acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of biomolecules to distinguish between D and L configurations is crucial in all biological events, including cell‐cell, cell‐proteins and cell‐bacterial interactions . Nearly all mammalian lectins prefer the D‐form over the L‐form of carbohydrates, the exceptions to this is L‐fucose and L‐iduronic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of biomolecules to distinguish between D and L configurations is crucial in all biological events, including cellcell, cell-proteins and cell-bacterial interactions. [1][2][3][4][5][6][7] Nearly all mammalian lectins prefer the D-form over the L-form of carbohydrates, the exceptions to this is L-fucose and L-iduronic acids. L-fucose is found in mammalian cell surfaces in the form of Lewis x/a -and sialyl Lewis x/a -carbohydrates and are pivotal ligands for C-type and selectin lectins.…”
Section: Introductionmentioning
confidence: 99%
“…These surface‐associating immune cells were less adherent, anchored poorly, and showed lower levels of activity on the d ‐enantiomer surface than the l ‐enantiomer surface. Chiral effects impinge on neuronal growth, and a study showed that l ‐cysteine reduced neuronal growth and prevented attachment; by contrast, d ‐cysteine facilitated growth and attachment . Consequently, polymer surface chirality affects the cell fate mediated via protein adsorption characteristics together with its own display of chirality .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Chirality is an intriguing and intrinsic feature of life and is extensively found in most biomolecular components of living organisms,s uch as DNA, proteins,p hospholipids,a nd sugars. [9][10][11][12][13] Nevertheless, whether chirality influences the translocation behavior of proteins remains unclear.T herefore,itisofgreat importance to investigate the fundamental question:h ow chirality influences the protein transport process? [9][10][11][12][13] Nevertheless, whether chirality influences the translocation behavior of proteins remains unclear.T herefore,itisofgreat importance to investigate the fundamental question:h ow chirality influences the protein transport process?…”
mentioning
confidence: 99%
“…[5][6][7][8] Accumulating evidence has indicated that most biological and physiological processes involve intermolecular interactions that are mediated by chirality. [9][10][11][12][13] Nevertheless, whether chirality influences the translocation behavior of proteins remains unclear.T herefore,itisofgreat importance to investigate the fundamental question:h ow chirality influences the protein transport process?…”
mentioning
confidence: 99%